Осадження наноструктурованих металів (Ag, Au, Pd) на кремній електролізом і гальванічним заміщенням з розчинів DMSO та DMF - Шепіда, Мар'яна Володимирівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.17.03 – технічна електрохімія. – Національний технічний університет “Харківський політехнічний інститут”, Міністерство освіти і науки України, Харків, 2019. У роботі розвинуто науковий напрям керованого електрохімічного осадження наноструктурованих осадів металів (Ag, Au, Pd) на поверхню кремнію електролізом та методом гальванічного заміщення у середовищі органічних апротонних розчинників. Встановлено, що поєднання імпульсного режиму електролізу та неводного середовища сприяє формуванню наночастинок металів. Досліджено вплив концентрації іонів відновлювальних металів на геометрію наночастинок та їх розподіл по поверхні підкладки. Вивчено залежність розмірів наночастинок металів від тривалості процесу гальванічного заміщення. Вияснено закономірності впливу температури процесу, типу поверхні кремнію, природи органічних розчинників на формування наноструктурованих осадів металів (Ag, Au, Pd) та їх морфологію. Комплекс отриманих експериментальних даних дозволив модифікувати поверхню кремнію наночастинками металів для одержання наноструктур кремнію та плазмонно-активних поверхонь на їх основі. Реалізований у роботі методи імпульсного електролізу дозволяє одержати фіксовані на поверхні підкладки наноструктуровані осади металів заданої форми та розмірів для виготовлення високочутливих сенсорів з подальшим перетворенням сонячного світла в електричну енергію.

Thesis for the degree of candidate of chemical sciences (PhD) in speciality 05.17.03 – Technical Electrochemistry. – Lviv Polytechnic National University, Lviv. – Kharkiv Polytechnic Institute National Technical University, Ministry of education and science of Ukraine, Kharkiv, 2019. The scientific direction of the controlled electrochemical deposition of nanostructured metals (Ag, Au, Pd) on the silicon surface by electrolysis and the method of galvanic replacement in the medium of organic aprotic solvents is developed. It is established that the combination of the pulsed mode of electrolysis and non-aqueous medium promotes the formation of metal nanoparticles. The effect of the concentration of reducing metal ions on the geometry of the nanoparticles and their distribution on the surface of the substrate were investigated. The dependence of the size of metal nanoparticles on the duration of the process of galvanic replacement was studied. The regularities of the influence of the process temperature, the type of silicon surface, the nature of organic solvents on the formation of nanostructured metal sediments (Ag, Au, Pd) and their morphology are revealed. Herefore, the value of cathode potentials, the duration of electrodeposition and the concentration of metal ions are the main factors influencing the morphology of the metal precipitate and the geometry of its structural particles, which is crucial for the controlled formation of nanostructures based on them. The dependence of geometry of nanoparticles of metals (Ag, Au, Pd) and sediment morphology on electrodeposition conditions (values of cathode potential, concentration of metal ions and process duration) are investigated. It is established that with increasing values of these values there is a tendency to form sediments from discrete particles (from 30 nm to 70 nm) to agglomerates (from 120 nm to 200 nm) and nanoporous films. It is established that the nature of the metal ion, its concentration, temperature and duration of the process of galvanic replacement are the main factors influencing the size of the deposited nanoparticles and the parameters of the controlled formation of Si/MNPs nanostructures. Nanoscale galvanic replacement of silver, palladium, and gold in organic aprotic solvents ensures the formation of nanostructured metal deposits on the silicon surface without the occurrence of side processes. This makes it possible to obtain Si/MNPs systems with nanoparticle sizes up to 100 nm with a relatively small size range. A schematic technological scheme of deposition of metal nanoparticles (Ag, Au, Pd) on silicon electroplating substitution in the environment of organic aprotic solvents was proposed, which allowed to obtain silicon/nanomaterial nanomaterials with functional properties. It has been found that Si/PdNPs, Si/AuNPs systems are more effective in forming silicon nanostructures than Si/AgNPs, due to the difference in metals by the values of standard electrode potentials. The results of the research trials at the “Research Center of the Committee of Forensic Expertise of the Republic of Belarus” proved the effectiveness of the materials obtained for the highly sensitive sensors. The results of work in the educational process of the Department of Chemistry and Technology of Inorganic Substances of NU “Lviv Polytechnic” in teaching the disciplines on the specialty 05.17.03 – “Technical Electrochemistry” were introduced.
Deposition of nanostructured metals (Ag, Au, Pd) on silicon electrolysis and electroplating from DMSO and DMF solutions
Keywords: автореферат дисертації; наноструктуроване срібло; наноструктуроване золото; наноструктурований паладій; поверхня кремнію; електроліз; імпульсний струм; гальванічне заміщення; апротонні розчинники; наноструктури кремнію; nanostructured silver; nanostructured gold; nanostructured palladium; silicon surface; electrolysis; pulse current; galvanic replacement; aprotic solvents; silicon nanostructures; 621.35